Stable isotope (B, H, O) and mineral-chemistry constraints on the magmatic to hydrothermal evolution of the Varuträsk rare-element pegmatite (Northern Sweden) - Siegel, Karin; Wagner, Thomas; Trumbull, Robert B.; Jonsson, Erik; Matalin, Gabriella; Wälle, Markus; Heinrich, Christoph A.; id_orcid:0 000-0001-5838-4607 (Chemical Geology, 2016)
ISSN:0009-2541 ISSN:1872-6836